Epidemiology of spontaneous pneumothorax: gender-related differences. Issue 7 (27th April 2015) - Bobbio, Antonio; Dechartres, Agnès; Bouam, Samir; Damotte, Diane; Rabbat, Antoine; Régnard, Jean-François; Roche, Nicolas; Alifano, Marco
Abstract : Background: Epidemiology of spontaneous pneumothorax has been scantily studied. We aimed to assess the incidence of spontaneous pneumothorax and describe patients' characteristics with respect to age, sex, seasonal occurrence, primary or secondary character, surgical management and rehospitalisations on a large-scale database. Methods: Data from all patients aged ≥14 years and hospitalised with a diagnosis of non-traumatic pneumothorax in France from 2008 to 2011 were retrieved from the National Hospitalisation Database. Results: There were 59 637 hospital stays corresponding to 42 595 patients. Twenty-eight per cent of patients were rehospitalised at least once during the 4-year period. Annual rate of pneumothorax could be estimated at 22.7 (95% CI 22.4 to 23.0) cases for 100 000 habitants. The women to men ratio was 1:3.3. Mean age was significantly higher in women than in men (41±19 vs 37±19 years, p<0.0001). No seasonal variation was observed. A surgical procedure was performed in 14 352 hospital stays (24%). In the group of patients aged <30 years, there was no statistical difference between men and women with regard to type of pneumothorax (primary or secondary), type of hospitalisation unit (surgery vs medicine), treatment modality (surgery or not), intensive care unit (ICU) admission and hospital stay duration. Rehospitalisation was more frequent in women than in men (56% vs 52%, p<0.0001). In the 30–49 years age group, surgery and rehospitalisation were more frequent in women than in men (each, p<0.001). In the 50–64 years age group, surgical procedures and rehospitalisations were more frequent in men than in women (p=0.002 and p<0.0001, respectively). Conclusions: Sex and age are determinant factors in the course of spontaneous pneumothorax.